Influência do ciclo menstrual sobre o limiar de variabilidade da frequência cardíaca em mulheres adultas - Dias, Nicolle Souza (2024)
The objective of the present study was to compare the heart rate variability threshold (HRVT) and perceived exertion during an incremental test in the luteal and early follicular phases of the menstrual cycle (MC) in adult women. Sixteen eumenorrheic women (age, 28.8 ± 6.7 years) performed a maximal effort test, starting with a load of 50W with increments of 25W every two minutes until voluntary exhaustion. The rating of perceived exertion (RPE) was recorded in the last 30 seconds of each stage using the Borg scale of 6–20 (BORG, 1982), and R-R intervals were collected throughout the tests using a Polar® chest sensor, model H10. A Student’s t-test for independent samples was used to compare the phases. The Wilcoxon test was used to compare weekly caloric expenditure via IPAQ, RPE, the BRUMS psychometric scale, the rate of increase in RPE relative to test time, and the load. Caloric expenditure during the week preceding the tests showed no statistical difference (P > 0.05). At the thresholds, no statistical differences were observed for load (W) and heart rate (HR) (P > 0.05). RPE showed a statistical difference (P = 0.03) in the HRVT for the parasympathetic autonomic indicators SD1/rMSSD, being higher in the follicular phase compared to the luteal phase. The rate of increase in RPE relative to test time in seconds (P = 0.03) and load (P = 0.021) showed statistical differences, being lower in the follicular phase; in other words, during the test in the follicular phase, participants reported a lower rate of increase in RPE for the effort performed. A significant difference was observed in the BRUMS psychometric scale. Participants reported higher values for their perceptions of fatigue during the follicular phase and of vigor during the luteal phase. No significant differences were found in physiological variables and performance during a maximal incremental test on a cycle ergometer with eumenorrheic women in the luteal and early follicular phases. However, during the early follicular phase, participants reported greater exertion for performing the same task compared to the luteal phase, indicating greater vagal withdrawal in the HRVT SD1/rMSSD.